Analisis Pendapatan Usahatani Kacang Tanah (Studi Kasus di Subak Gerokgak, Kecamatan Gerokgak, Kabupaten Buleleng) - JUNIASIH, NI KADEK; DARMAWAN, DWI PUTRA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Peanut Farming Income Analysis (Case Study in Subak Gerokgak, Gerokgak District, Buleleng Regency).  Peanuts are an agribusiness commodity that has high economic value and is a source of protein for the Indonesian population. One of the crops that are grown by farmers in Subak Gerokgak is peanuts. This study aims to determine the income, R / C ratio and constraints in peanut farming in Subak Gerokgak, Gerokgak District, Buleleng Regency. The location selection and determination of the 25 respondent farmers were carried out by using purposive sampling technique. The results of the analysis show that one planting season requires production costs of Rp. 7,696,728.00 per 1.07 ha, resulting in revenues of Rp. 20,116,440.00 per 1.07 ha, and income of Rp. 12,419,712.00. The R / C ratio per 1.07 ha is 1.61 and the obstacles faced by farmers are technical constraints. Farmers should reduce production costs, especially labor costs outside the household and improve pests management technique.